Kallikrein-related peptidases (KLKs) as emerging therapeutic targets: focus on prostate cancer and skin pathologies. (2nd July 2016) - Avgeris, Margaritis; Scorilas, Andreas
ABSTRACT: Introduction: Tissue kallikrein and the kallikrein-related peptidases (KLKs) constitute a family of 15 homologous secreted serine proteases with trypsin- or chymotrypsin-like activities, which participate in a broad spectrum of physiological procedures. Deregulated expression and/or activation of the majority of the family members have been reported in several human diseases, thereby making KLKs ideal targets for therapeutic intervention. Areas covered: In the present review, we summarize the role of KLKs in normal human physiology and pathology, focusing on prostate cancer and skin diseases. Furthermore, we discuss the recent advances in the development of KLK-based therapies. A great number of diverse engineered KLKs inhibitors with improved potency, selectivity and immunogenicity have been synthesized by redesigning examples that are endogenous and naturally occurring. Moreover, encouraging results have been documented using KLKs-based vaccines and immunotherapies, as well as KLKs-mediated activation of pro-drugs. Finally, KLKs-targeting aptamers and KLKs-based imaging tools represent novel approaches towards the exploitation of KLKs' therapeutic value. Expert opinion: The central/critical roles of KLK family in several human pathologies highlight KLKs as attractive molecular targets for developing novel therapeutics.